2020
DOI: 10.2147/opth.s262167
|View full text |Cite
|
Sign up to set email alerts
|

<p>Contributions of Anterior Corneal and Ocular Residual Astigmatism to Autorefraction Astigmatism in a Myopic Adult Sample</p>

Abstract: Aim To evaluate the contributions of anterior corneal and ocular residual astigmatism to autorefraction astigmatism in adult myopic and myopic astigmatic subjects and how these compensate each other. Subjects and Methods This retrospective study was completed in private eye centre, Ismailia, Egypt, between September 2017 and November 2019. The study included eyes with myopia (0.5 to 10.0D) or myopic astigmatism (0 to 8.5D). The refractive errors, including autorefractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…The outcome of refractive and cataract surgeries depends upon insight into the distribution of different astigmatic components, their relationship, and the counteractive or superimposed effect between ACA and ocular residual astigmatism based on the type of astigmatism, ie, ATR or WTR. 23 , 24 Interestingly, a negative correlation between residual astigmatism and preoperative ACA was observed in this study, congruent to the findings of Lin J who found that ACA was offset by ocular residual astigmatism in 84.8% (140) of eyes. 24 This can be due to the greater appearance of the posterior cornea’s ATR astigmatic component in cases of low WTR astigmatism of the anterior cornea as a consequence of steep meridian incision from the superior side.…”
Section: Discussionsupporting
confidence: 92%
“…The outcome of refractive and cataract surgeries depends upon insight into the distribution of different astigmatic components, their relationship, and the counteractive or superimposed effect between ACA and ocular residual astigmatism based on the type of astigmatism, ie, ATR or WTR. 23 , 24 Interestingly, a negative correlation between residual astigmatism and preoperative ACA was observed in this study, congruent to the findings of Lin J who found that ACA was offset by ocular residual astigmatism in 84.8% (140) of eyes. 24 This can be due to the greater appearance of the posterior cornea’s ATR astigmatic component in cases of low WTR astigmatism of the anterior cornea as a consequence of steep meridian incision from the superior side.…”
Section: Discussionsupporting
confidence: 92%